Neurodegenerative disorders, bullous pemphigoid and psoriasis: a comparative study in ethnic Poles indicates that Parkinson’s disease is more relevant to bullous pemphigoid - Bartkiewicz, Paweł; Gornowicz-Porowska, Justyna; Pietkiewicz, Paweł P.; Świrkowicz, Anna; Bowszyc-Dmochowska, Monika; Dmochowski, Marian (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction: Bullous pemphigoid (BP) is an autoimmune blistering dermatosis of the elderly with autoimmunity to hemidesmosomal proteins, BP180 and BP230, which are expressed also in neuronal tissue. Aim : The aim here was to retrospectively compare the prevalence of neurodegenerative disorders (ND), particularly Parkinson’s disease (PD), unspecified conditions manifesting as dementia and stroke, in two groups of ethnic Poles, with BP and with psoriasis (Ps), in order to obtain data whether BP is more prone to coexist with ND than Ps in the elderly. Psoriasis was chosen in this comparative study as it was considered to be a paradigm of cutaneous disease with systemic manifestations. Material and methods : The available medical records of 96 BP patients and 149 Ps patients over 70 years of age were analyzed for the presence of ND. Results : There were no statistically significant differences in prevalence of ND without specifying the type and ND types analyzed between BP and Ps groups, except for a higher prevalence of PD in the BP group. Conclusions :Thus, regarding population aging and increasing incidence and prevalence of BP corresponding with that phenomenon in various ethnicities, it appears justified to expand studies of a possible immunopathogenic relationship, appearing to be PD-related, between BP and ND.